Purification of fructosyltransferase (FTase) from Aspergillus Niger to enhance production of Fructooligosaccharides (FOS) as a food additive - Muhamad Aliff, Ramli (2012)
Nowadays,worldwide consumers are becoming increasingly aware of the relationship between food or food constituents and health.In response to an increasing demand from the consumer,fructooligosaccharides (FOS) have emerged primarily because of its functional properties rather than sweeteners.The enzyme source synthesis can be divided into two classes which are from plant and microorganism. Microorganism producing FOS from FTase had captured much attention from industrial level due to mass production and controlled environment rather than FOS produced from plant. Many researchers produced crude FTase enzyme to produce FOS. In view of that,purification of crude enzyme from microfungi is studied in order to obtain high yield of FOS.This study is carried out using molasses as a substrate in the fermentation process to produce crude enzyme from microorganism.The series of purification step will be done in order to purify the enzyme and to determine the characteristic of purified enzyme. By using an extracellular enzyme which is fructosyltransferase (FTase) from selected micro fungi,the FOS can be produced commercially from sucrose.The enzyme was able to transfer the fructosyl group from sucrose as donor producing corresponding series of FOS: 1-kestose,nystose and fructosylnystose.Although these proteins differ in their subunit structure,molecular weight,chemical susceptibility and substrate specificity, they all display both hydrolytic and transfer activities which limit the FOS production to the use of high sucrose concentration.The optimum pH and temperature for activity of FTase is between 5 to 6.5 and 50 °C to 60 °C with yield of 125 U/mL when crude FTase is used and 136.7 U/mL when purified FTase is used.For the purification studies of FTase, different micro fungi will produce different characteristic of enzyme.The enzyme was able to transfer fructosyl groups from sucrose and then catalyze the formation of short chain FOS.